2006
DOI: 10.1167/iovs.05-1415
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic Membrane for Ocular Surface Reconstruction: Donor Variations and the Effect of Handling on TGF-β Content

Abstract: TGF-beta1 is present in various regulatory forms in the AM. A degree of intermembrane and intramembrane variation is modified by handling. Unless a standardized protocol is adopted that delivers a membrane with consistent constituents, clinical outcomes may vary and comparisons may be invalid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
103
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(110 citation statements)
references
References 36 publications
7
103
0
Order By: Relevance
“…However, there was a reduction in acute pain and more rapid epithelisation in moderate burns. 43,44 No benefit was confered in severe burns. No difference was found in the treatment of neurotrophic ulcers compared with conventional therapies.…”
Section: Limitations Of Ammentioning
confidence: 99%
See 1 more Smart Citation
“…However, there was a reduction in acute pain and more rapid epithelisation in moderate burns. 43,44 No benefit was confered in severe burns. No difference was found in the treatment of neurotrophic ulcers compared with conventional therapies.…”
Section: Limitations Of Ammentioning
confidence: 99%
“…Further variations exist dependent on the foetal sex, health, gestational age, and specifics relating to labour. Hopkinson et al 44 showed the relationship of handling and processing of AM on the possible eventual alterations in the final make of the AM with regard to TGFb. Similar variations have been reported by Gicquel et al 47 with regard to epidermal growth factor.…”
Section: Limitations Of Ammentioning
confidence: 99%
“…[32][33][34][35][36] However, the high inter-and intra-tissue variability in morphological, chemical, and optical properties limit the use of the human amniotic membrane in clinical settings. [37][38][39] Alternatively, human donor corneal stromal tissues have been proposed as substrates for human corneal epithelium growth, displaying, in vitro, features similar to the native limbal epithelium. 40 The lack of corneal tissue donor availability significantly affects its clinical potential for corneal reconstruction.…”
Section: Corneal Epitheliummentioning
confidence: 99%
“…AM is generally rendered non-viable during preservation, either by drying or freezing. [29] As a non-viable tissue, currently used surgically, AM is an ideal candidate for terminal sterilization.…”
Section: Challenges Of Tbtm Manufacturing and Risk Of Contaminationmentioning
confidence: 99%